Hubungan Vulva Hygiene Dengan Terjadinya Flour Albus Pada Remaja Putri Di SMP Negeri 55 Kota Makassar - Rahmani, Siti; Alfyan Rahim; Nurkasibah Kurniawati (Journal of Pubnursing Sciences, 2024)
A reproductive problem that is often experienced, especially by women, is vaginal discharge. According to the World Health Organization (WHO), in 2022 around 75% of women in the world will experience vaginal discharge at least once in their lifetime. If abnormal (pathological) fluoride albus is left untreated or treatment is not given immediately, it will result in an infection that can spread into the uterus and infect the ovaries, which can cause infertility and cervical cancer. With this impact, young women need to pay attention to personal hygiene behavior. Objective: to analyze the relationship between vulva hygiene and the occurrence of vaginal discharge in teenagers at SMP Negeri 55 Makassar. Method: This research used quantitative correlation research methods by using a Cross-Sectional Study with Purposive Sampling techniques. Results: The results of the research that has been carried out show a significant value of 0.000 < α (0.05), so there is a relationship between vulva hygiene and the occurrence of flour albus in young women. Conclusion: There is a relationship between vulva hygiene and the occurrence of flour albus in young women at SMP Negeri 55 Makassar City. Suggestion: It is hoped that this research can be used as a reference and research should be conducted on a broader subject